BS IEC 60335-2-114. Household and similar electrical appliances. Safety. Part 2-114. Particular requirements for selfbalancing personal transport devices for use with batteries containing alkaline or other non-acid electrolytes (1st February 2022) - British Standards Institution
No abstract available